Luke; the boy who wanted to make people well - Battle, Gerald N.; Teichman, Dorothy (Waco, Tex., Word Books, 1972)
A fictionalized biography of the Greek physician who became a follower of Jesus.
Keywords: Luke, -- Saint -- Juvenile fiction; Luke, -- Saint -- Fiction